2018
DOI: 10.1371/journal.pntd.0006282
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trachoma in school children in the Marajó Archipelago, Brazilian Amazon, and the impact of the introduction of educational and preventive measures on the disease over eight years

Abstract: Trachoma is the leading infectious cause of blindness in the world and is associated with precarious living conditions in developing countries. The aim of the present study was to evaluate the prevalence of trachoma in three municipalities of the Marajó Archipelago, located in the state of Pará, Brazil. In 2008, 2,054 schoolchildren from the public primary school system of the urban area of the region and their communicants were clinically examined; in 2016, 1,502 schoolchildren were examined. The positive cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
6
9
1
Order By: Relevance
“…In Pernambuco and in the mesoregions of the Metropolitan Region of Recife and Sertão do São Francisco, the more rooms that there were in a household, the greater the risk of trachoma was. This result goes against the results found in other surveys conducted in Brazil, which indicated that a smaller number of rooms presented a higher risk of trachoma [10,29].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In Pernambuco and in the mesoregions of the Metropolitan Region of Recife and Sertão do São Francisco, the more rooms that there were in a household, the greater the risk of trachoma was. This result goes against the results found in other surveys conducted in Brazil, which indicated that a smaller number of rooms presented a higher risk of trachoma [10,29].…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted in Brazil have shown that school-age children (5-9 years) have greater chances of presenting trachoma [10,28,29], thus corroborating the results of the present study. Last et al (2014) [18] showed that cases occurred predominantly among children between 0 and 5 years of age, in a household survey conducted in Guinea-Bissau.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations